S4: Top-k Spreadsheet-Style Search for Query Discovery - Psallidas, Fotis; Ding, Bolin; Chakrabarti, Kaushik; Chaudhuri, Surajit (Proceedings of the ACM SIGMOD International Conference on Management of Data (SIGMOD 2015), 2015)
An enterprise information worker is often aware of a few example tuples that should be present in the output of the query. Query discovery systems have been developed to discover project-join queries that contain the given example tuples in their output. However, they require the output to exactly contain all the example tuples and do not perform any ranking. To address this limitation, we study the problem of efficiently discovering top-k project join queries which approximately contain the given example tuples in their output. We extend our algorithms to incrementally produce results as soon as the user finishes typing/modifying a cell. Our experiments on real-life and synthetic datasets show that our proposed solution is significantly more efficient compared with applying state-of-the-art algorithms.